Embolisation of spinal dural arteriovenous fistulae with Onyx. - Warakaulle, DR; Aviv, R; Niemann, D; Molyneux, A; Byrne, J; Teddy, P (2003)
Surgery is currently the standard treatment for spinal dural arteriovenous fistulae (DAVF). Endovascular embolisation of these lesions using N-butyl cyanoacrylate (NBCA) has a high success rate. Onyx is a new liquid embolic agent whose viscosity makes it suitable for treatment of spinal DAVF where penetration into the proximal radicular vein is required. It is delivered with greater control than NBCA without the necessity for rapid withdrawal of the catheter and may therefore overcome some of the drawbacks of NBCA. We report two patients who underwent Onyx embolisation of spinal DAVF; to our knowledge this is the first such report.